Curriculum Management Innovation to Prepare Superior Human Resources in the Era of Industrial Revolution 4.0 - Anco (Universitas Mohammad Husni Thamrin, 2025)
The Fourth Industrial Revolution (Industry 4.0) has had a significant impact on various sectors of life, including education. Advances in cutting-edge technologies, such as Artificial Intelligence (AI), the Internet of Things (IoT), and big data, have fundamentally transformed the learning process. Today's education no longer focuses solely on knowledge transfer but rather emphasizes the development of 21st-century skills, such as critical thinking, creativity, and adaptability (Kayembe et al., 2019). This transformation has also triggered a paradigm shift in the education system, from conventional learning methods to a technology-based digital approach (Haleem et al., 2022). The purpose of this study is to analyze various innovative strategies in curriculum management implemented in educational institutions to prepare graduates who are adaptive, creative, and possess 21st-century skills. This study uses a literature review method by examining various scientific sources and previous research results relevant to curriculum reform in the era of globalization and the Fourth Industrial Revolution. The study's findings indicate that innovative strategies in curriculum management include the application of digital technology in the learning process, the use of project-based learning (PBL) models, and the integration of soft skills such as communication, collaboration, and critical thinking with hard skills aligned with industry needs. These findings indicate that educational institutions need to design flexible, contextual, and future-oriented curricula to produce graduates who are ready to face global challenges.